Development of a remote laboratory for an electronic circuit design and analysis course with increased accessibility by using speech recognition technology - SARIKAŞ, ALİ; BULDU, ALİ; YAYLA, AYŞE; KORKMAZ, HAYRİYE (WILEY, 2021)
When the curricula of engineering undergraduate programs are examined, it can be seen that experimentation plays a very important role and the learning outcomes of the courses are mostly dependent on practical abilities. However, there may be a few who cannot use their hands permanently or temporarily among the students who are attending these courses. Therefore, the participation of disabled students in this part of the course has always been a problem. In this paper, a remote laboratory application that aims to increase the accessibility of electronic circuit design and analysis courses by using speech recognition technology is introduced. This laboratory is designed for hands-free operation and enables students to analyze the electronic circuits by speaking. Google Web Speech API was used for speech recognition and the user interface was designed using Adobe Flash Professional. The parameters are sent to the ASP.NET page by using ActionScript 2.0 programming language. The application developed by using C# programming language enables programming the experimental hardware that includes a signal generator, a Raspberry Pi 2 with a camera, an oscilloscope, and a new test card. In the Raspberry Pi 2, Python programming language was used to select the desired experiment from those present on the board and to control digitally programmable circuit components such as digital potentiometers or parameters such as the DC reference voltage level. When the student successfully completes the predefined experimental procedures, an automatically generated e-mail is sent to the instructor including the student's username, log-in time, the oscilloscope screenshots, and ideal experimental results.
Keywords: disabled students; electronics circuit analysis remote lab; increased accessibility; speech recognition; Web Speech API; STUDENTS; SYSTEM